Threshold point utilisation in juror decision-making. Issue 1 (2nd January 2019) - Curley, Lee J.; MacLean, Rory; Murray, Jennifer; Pollock, Andrew C.; Laybourn, Phyllis
Abstract : This study aims to identify whether a model of juror decision-making (i.e. the threshold point model) that encompasses both rational and intuitive decision-making exists. A total of 60 participants were selected who are eligible for jury duty in Scotland. These individuals read nine vignettes and rated the evidence of each vignette separately by placing the evidence in either a guilty, a not guilty or a not proven (a verdict type specific to Scotland) counter. Participants were asked after being presented with each piece of information to state how likely they thought the suspect was of being guilty, on a scale from 1 to 100. The data are best described using a flexible model (i.e. a diffusion model) that allows for information integration. Future research should examine whether or not the diffusion model can explain cognitive fallacies, such as confirmation bias, that are commonly studied in decision science.